1999
DOI: 10.1002/(sici)1096-9918(199908)28:1<250::aid-sia587>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Co-Al-O magnetic thin films by combined use of XPS, XRD and EPMA

Abstract: Several Co–Al–O alloy thin films with different physical properties were prepared by reactive r.f. sputtering of Co85Al15 and Co70Al30 alloy targets in Ar + O2 atmospheres and were characterized by XPS, x‐ray diffraction (XRD) and electron probe microanalysis (EPMA). The alloy films contained metallic Co, mainly of hexagonal phase, and also CoO. The Al oxide in the Co–Al–O thin films did not give any detectable diffraction peaks. The EPMA results showed that [Al]/([Co] + [Al]) ratios, where [M] denotes molar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…In order to resolve those issues and obtain optimal soft magnetic properties, knowledge of the nanostructure of the film is required. In previous studies of nanogranular films, a possible intermixing of magnetic elements into the amorphous matrix was often noted [7][8][9][10]. A magnetic element dispersed in the matrix can influence the magnetic properties via a reduction of magnetization, a modulation of magnetic coupling, and/or a change in transport properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…In order to resolve those issues and obtain optimal soft magnetic properties, knowledge of the nanostructure of the film is required. In previous studies of nanogranular films, a possible intermixing of magnetic elements into the amorphous matrix was often noted [7][8][9][10]. A magnetic element dispersed in the matrix can influence the magnetic properties via a reduction of magnetization, a modulation of magnetic coupling, and/or a change in transport properties [11].…”
Section: Introductionmentioning
confidence: 99%
“…The high-resolution Co 2p and V 2p XPS spectra are shown in Figure 4, and the Co 2p 3/2 electron binding energy (Figure 4a) is 781.78 eV, corresponding to the Co +2 state, indicating the cobalt oxide (CoO) formation. 39 The oxidation of metal nanoclusters during XPS sampling procedure is a known phenomenon, 38 as there is no indication of CoO formation in the XRD. Additionally, the absence of any metal oxides peak in the Raman spectrum of VCKB also confirmed that metal oxide is formed only during the XPS sampling procedure, as Raman is a strong tool to test the existence of CoO.…”
Section: Resultsmentioning
confidence: 99%
“…The XPS was used for examining the composites′ surface configuration and chemical valence. The high-resolution Co 2p and V 2p XPS spectra are shown in Figure , and the Co 2p 3/2 electron binding energy (Figure a) is 781.78 eV, corresponding to the Co +2 state, indicating the cobalt oxide (CoO) formation . The oxidation of metal nanoclusters during XPS sampling procedure is a known phenomenon, as there is no indication of CoO formation in the XRD.…”
Section: Resultsmentioning
confidence: 99%
“…18,20 The O 1s peak for Al-O bonding is at 531.6 eV, while the Co-O bonding peak is 530.4 eV for the fits. 21 However, as shown in background. The magnetic moment of the granules, however reduces in magnitude (by 25%) as shown in Fig.…”
mentioning
confidence: 91%
“…18,20 The O 1s peak for Al-O bonding is at 531.6 eV, while the Co-O bonding peak is 530.4 eV for the fits. 21 However, as shown in Fig 4(b) and (c), the O 1s spectra for both the cases (as deposited and after electric field application) can be fitted very well using a single Voigt function peak at the k-points. These calculations do not include the effects of the curvature, structural defects, and the relaxation which would be inevitably present in the experimental setup.…”
mentioning
confidence: 99%